Efek Fraksi Volume Dan Panjang Serat Terhadap Pengujian Tarik Dan Impak Menggunakan Serat Daun Nanas Smooth Cayenne - Yuliyanto, Yuliyanto; Ramli, Ramli; Ventani, Embun (Manutech : Jurnal Teknologi Manufaktur, 2023)
Bangka Belitung is one of the provinces with the largest pineapple production in Sumatra, but the pineapple leaves have not been processed and are still considered waste. Currently, the use of pineapple trees is only for the fruit. Even though pineapple leaves have very strong fiber and can be used as a composite of natural fibers. Composites reinforced with natural fibers have excellent corrosion resistance properties, as well as lower production costs, and are considered more environmentally friendly. The research objective was to obtain the highest tensile and impact testing values ??for volume fractions of 15%, 20%, 25%, 30%, and 35% with 5% NaOH alkaline treatment for 2 hours. Making samples using the hand lay-up method. The analysis was carried out using the direct experimental design method, in which the effect of the ratio of the volume fraction of the fiber after immersion in 5% NaOH for 2 hours on the tensile strength and impact strength would be seen. The result is the highest tensile strength of 52.6 MPa at 25% fiber volume fraction and a decrease in tensile strength at 30% and 35% volume fraction. The lowest tensile strength was at 35% volume fraction with a tensile test strength value of 24.7 Mpa, while the highest impact test results were 26.5 kj/m² at 30% volume fraction, while the lowest impact strength was 11 kj/m². This is because more and more distribution of fiber in the resin in each composite will strengthen the bond between the matrix and the fiber which causes the composite to be sturdy and not brittle, but if the fiber is above 30% it will result in a decrease in strength due to imperfect bonding of the resin and fiber. Vice versa, a few fibers will make the reinforcing bond unbalanced and tend to decrease its strength. For fiber test results above 20%, it can be used as a new composite material for making helmets according to SNI standards.